Analysis of The Implementation of E-ATAN in Improving Academic Performance at STAIN Bengkalis - Daffa Azura Nurrafina; Puspasari; Danial Akmal; Titin Sumarni (Interkoneksi: Journal of Computer Science and Digital Business, 2024)
The aim of this research is to improve academic performance at STAIN Bengkalis through the use of E-atan. This research uses a qualitative approach that collects data through interviews. The research subjects were students, teachers and administrative employees who were directly involved in using E-atan. The research results show that the use of E-atan has improved various aspects of academic performance. This includes easier academic administration, easier access to academic information, and better interaction between teachers and students. However, the research also uncovered several issues, such as the need for additional user training and improved technology infrastructure. Overall, the results show that E-atan has enormous potential to help improve the academic performance of STAIN Bengkalis if used and managed well.